Comparison of the accuracy of cannulated pedicle screw versus conventional pedicle screw in the treatment of adolescent idiopathic scoliosis: A randomized retrospective study - Yilar, Sinan (Medicine (Baltimore), 2019)
BACKGROUND: Pedicle screws are commonly used to treat adolescent idiopathic scoliosis (AIS). Many studies have discussed the rates and effects of pedicle screw misplacement. In this study, to increase the accuracy rate, cannulated pedicle screws were inserted into the periapical vertebrae, highly rotated vertebrae, and vertebrae with very thin pedicles in a single patient group. We compared these results with those of a patient group who underwent conventional pedicle screw placement. METHODS: Twenty-eight AIS patients treated surgically between 2015 and 2017 with cannulated pedicle screws or conventional pedicle screws were included. Group 1 (n = 15) received cannulated pedicle screws, whereas group 2 (n = 13) received conventional pedicle screws. Postoperative computed tomography scans were used to evaluate pedicle screw position. Pedicle perforation was assessed using the classification by Rao et al: grade 0, no perforation; grade 1, only the threads outside the pedicle (less than 2 mm); grade 2, core screw diameter outside the pedicle (2–4 mm); and grade 3, screw entirely outside the pedicle. Medial screw malposition was measured between the medial pedicle wall and the medial margin of the screw. Lateral screw malposition was measured between the lateral corpus wall and lateral screw margin. RESULTS: Placement accuracy of 703 screws (group 1, 376; group 2, 327) was evaluated. A total of 142 (20.1%) pedicle screw perforations occurred: 63 (17.1%) in group 1 and 79 (25%) in group 2 (P < .05). There was no statistically significant intergroup difference in medial perforation (group 1, 34 [9%] vs group 2, 31 [10%]). Lateral perforation was significantly less common in group 1 (n = 29; 7.7%) than in group 2 (n = 4; 14.7%) (P = .0002). CONCLUSIONS: The use of cannulated screws to treat AIS decreases perforation and complication rates. Although it did not significantly lower the medial perforation rate, it dramatically reduced the lateral perforation rate. The use of cannulated screws enables intraoperative confirmation of placement accuracy. Our data suggest that cannulated pedicle screw use to treat AIS is safer and more efficient.